2018
DOI: 10.1002/bmc.4194
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of acyclovir in dermal interstitial fluid and human serum by ultra‐high‐performance liquid–high‐resolution tandem mass spectrometry for topical bioequivalence evaluation

Abstract: Time-concentration curves for the topical anti-viral drug acyclovir can provide valuable information for drug development. Open flow microperfusion is used for continuous sampling of dermal interstitial fluid but it requires validated methods for subsequent sample analysis. Therefore, we developed a sensitive, selective and high-throughput ultra-high-performance liquid chromatography-high-resolution tandem mass spectrometry method to determine acyclovir in human dermal interstitial fluid and serum. We validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In our study, we investigated the RR and AR of six recombinant human cytokines of increasing molecular size using in vitro, ex vivo, and in vivo experiments. Due to their similarities to interstitial fluid and human skin [ 36 , 37 ], we used human serum and porcine skin, respectively, ex vivo and in vivo. Finally, we used excised human skin ex vivo and in vivo to find the most efficient perfusate (crystalloid or colloids) for investigating intercellular signalling in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we investigated the RR and AR of six recombinant human cytokines of increasing molecular size using in vitro, ex vivo, and in vivo experiments. Due to their similarities to interstitial fluid and human skin [ 36 , 37 ], we used human serum and porcine skin, respectively, ex vivo and in vivo. Finally, we used excised human skin ex vivo and in vivo to find the most efficient perfusate (crystalloid or colloids) for investigating intercellular signalling in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane and catheter were placed in syringes that were containing either Ringer’s lactate or human serum, which was chosen to mimic the interstitial fluid that surrounds the membrane when placed in living tissue. Although not identical, human serum is quite similar to interstitial fluid [ 36 , 37 ]. Furthermore, for the in vivo analysis, we subjected human and porcine skin cadavers and porcine dermal skin from anaesthetized domestic pigs to retrodialysis (i.e., inverse microdialysis).…”
Section: Introductionmentioning
confidence: 99%
“…Highresolution mass spectrometry (HRMS) can not only accurately measure the mass of ions, but also determine their elemental (and isotopic) composition accurately. Ultra-highperformance liquid chromatography-high resolution tandem mass spectrometry (UHPLC-HR MS/MS) was used for introduced into the determination of ACV in human dermal interstitial fluid and serum form, as reported by Schimek et al [76]. They indicated that the concentration range was from 0.1 ng/mL to 25 ng/mL with a sample volume of only 20 µL and validated the successful application with short-term and long-term sample stability data and the analysis of 5000 clinical trial samples.…”
Section: Liquid Chromatography/tandem Mass Spectrometry (Lc-ms/ms)mentioning
confidence: 99%
“…Stability was tested only for the prepared serum samples, as the short-term and long-term stability of serum, plasma, and standard solutions has already been published. [2,10,12,15,16,21,28] The stability of prepared serum…”
Section: Stability Studiesmentioning
confidence: 99%
“…Chromatographic methods, namely, HPLC with UV light [3,4,[9][10][11][12][13] or fluorescence detection, have been developed [1,14,15]. More recent methods are based on UHPLC/MS/MS [16][17][18][19]. UHPLC/MS/MS separation using sub-2 μm particle columns offers improved specificity and sensitivity and can reduce separation time while maintaining separation efficiency [20].…”
Section: Introductionmentioning
confidence: 99%